Exploring the Depths of Digital Marketing: A Systematic Literature Review on Segmentation, Targeting, Differentiation, and Positioning Strategies - Nashiroh, Abdillah Agustya Siwi; Shiddiqy, Isymayati Ash; Hidayat, Mohammad Nurul (IJBLE Scientific Publications Community Inc., 2024)
This research aims to find out in depth about digital marketing strategies, namely segmentation, targeting, positioning and differentiation strategies, using methods favorite announcing thing (Preferred Reporting Items) andmeta examinations (meta analysis) or commonly called the PRISMA method. using 4 (four) journal websites, namely Google Scholar, Sciencedirect, Emerald, and Taylor & Francis. The results of this research show that segmentation of a brand will have a sustainable competitive advantage. A product will have a competitive advantage if the product is considered important and unique by customers. Targeting is the process of evaluating each segment's attractiveness and then selecting one or more characteristics to serve. Targeting discusses the issue of how to select, select and reach the market.